'Self‐fumigation' of nests by an endangered avian host using insecticide‐treated feathers increases reproductive success more than tenfold. (2nd August 2020) - Alves, F.; Langmore, N.; Heinsohn, R.; Stojanovic, D.
Abstract: Parasites can cause great fitness cost to their hosts, however, their impact on host populations is often unknown. In healthy populations, parasites are not expected to cause declines, but they can be devastating to small and/or declining populations. Nest ectoparasites can have detrimental impacts on the breeding output of their hosts and are emerging as a threat to several endangered bird species. Therefore, finding cost‐effect ways to reduce the impact of parasites on endangered hosts is crucial. Although 'close‐order' management techniques available to manage nest parasites are effective, they are often expensive and might not be suitable for species that are intolerant of intensive manipulation. We tested a low cost, 'close‐order' management technique to control parasites and boost nest productivity in an endangered passerine. The endangered forty‐spotted pardalote Pardalotus quadragintus is exploited by an ectoparasitic fly Passeromyia longicornis, an obligate subcutaneous parasite of nestling birds. We offered adult pardalotes the opportunity to 'self‐fumigate' their nests by supplying feathers treated with insecticide with which to line their nests and tested whether this boosted nest productivity. Pardalotes readily incorporated the experimental feathers in nest building, and survival of hatchlings was significantly higher in nests lined with treated feathers (95%) compared to nests lined with control feathers (8%). This represents a substantially greater improvement in reproductive success than in previous experimental studies, offering the strongest evidence yet that self‐fumigation is a highly effective, simple and low cost 'close‐order' management technique for defending endangered birds against ectoparasites. Abstract : Nest ectoparasites can have detrimental impacts on the breeding output of their hosts and are emerging as a threat to several endangered bird species. We tested a low cost, 'close‐order' management technique to control parasites and boost nest productivity in the endangered forty‐spotted pardalote Pardalotus quadragintus. Forty‐spotted pardalotes' nestlings are exploited by an obligate subcutaneous parasite Passeromyia longicornis that causes severe mortality. We offered adult pardalotes the opportunity to 'self‐fumigate' their nests by supplying feathers treated with insecticide with which to line their nests and tested whether this boosted nest productivity. Pardalotes readily incorporated the experimental feathers in nest building, and survival of hatchlings was significantly higher in nests lined with treated feathers (95%) compared to nests lined with control feathers (8%). Our results show that self‐fumigation can be a highly effective management technique for defending endangered birds against ectoparasites.